Penerapan Vigenere Chipher Pada Aplikasi Pemesanan Tiket Bioskop - Anwar, Nanda Rosma; Putri, Riska; Oktapiana, Tiara (Prosiding Sains dan Teknologi, 2024)
Booking cinema tickets online has become an important part of the consumer experience in the entertainment industry. This journal presents the evolution of online cinema ticket booking systems, with a focus on technology, security, speed and user experience. With the development of technology, information security has become a crucial aspect that needs to be considered. This relates to the need for security and privacy in the exchange of sensitive information such as cinema ticket booking data. And threats to the confidentiality of customer data and online transactions are also increasing, requiring effective security methods. The application of steganography techniques using the Vigenere Cipher algorithm in the Least Significant Bit (LSB) method for cinema ticket ordering applications emerged as a solution for hiding secret information in image images. The Vigenere Cipher method was chosen because of its ability to encrypt text using a longer key than the Caesar Cipher method. This makes Vigenere Cipher more resilient to brute force attacks. This research aims to implement the application of the Vigenere Cipher in the LSB method of steganography in a cinema ticket ordering application. The focus of the research involves increasing the level of security in the storage and exchange of sensitive information, especially related to online cinema ticket purchase transactions. The method used in this research uses the Vigenere Cipher implementation in the LSB steganography method on image images. So the LSB method is the most popular steganography method. By exploiting the weaknesses of human visual senses in observing changes a little in the picture. The method is to replace the LSB bits of the pixel with message bits. This process involves inserting confidential data into the cinema ticket image without reducing the visual quality of the image. Evaluation is carried out on the strength of encryption, hiding capacity and integrity of the steganography image. The research results show that the application of Vigenere Cipher in the LSB method of steganography in cinema ticket ordering applications can significantly increase the level of information security. The process of inserting secret data was successfully carried out without significantly sacrificing image quality. However, this research also identified several challenges and limitations that need to be considered in its practical implementation.